Diversely functionalised carbohydrate-centered oligomers and polymers. Thermoresponsivity, lectin binding and degradability. (January 2015) - Congdon, Thomas; Wilmet, Charline; Williams, Rebecca; Polt, Julia; Lilliman, Mary; Gibson, Matthew I.
Graphical abstract: Highlights: A series of reactive oligomers/polymers based on methacrylated carbohydrates have been synthesis. Thiol-ene 'click' modification was employed to introduce thermoresponsive and carbohydrate functionality. The properties of these polymers were investigated. Abstract: Nature is capable of synthesizing perfectly defined, sequence-controlled oligomers and polymers, whereas synthetic polymerization methods inherently give rise to dispersity and limited reproducibility. This inherent dispersity provides a barrier to translation into biomedical applications and for probing material-biology interactions. Templating of polymers based upon biosynthesized cores offers a route to reproducible oligo/polymers if the template itself is readily available and highly tunable. Here oligosaccharides are employed as monodisperse scaffolds for the synthesis of highly functional biomaterials. The pendant hydroxyl units are converted to reactive methacrylates, which are themselves amenable for thiol-ene ('click') functionalization. Using this strategy, extremely well defined (MW /MN  < 1.05) polymers are prepared bearing thermoresponsive or lectin-binding moieties. The templatation strategy ensures identical polymers are obtained from each synthesis. Their thermoresponsive behavior and multivalent interactions with a bacterial lectin are studied as a function of the discrete number of functional groups. Due to the ester linkage, these polymers are also shown to be inherently degradable.